Combinaison de la resistance varietale et dinsecticides a base de neem pour controler les principaux insectes ravageurs du niebe dans la region centrale du Burkina Faso - Ba, N.M.; Dabiré, C.B.; Drabo, I.; Sanon, A.; Tamo, Manuele (2008)
Insect pests are important constraints to cowpea production in central Burkina Faso. The main goal of this study was to provide an IPM strategy based on combination of resistant varieties to the pod sucking bug, and the application of neem seed extract against flower thrips (Megalurothrips sjostedti) and pod borers (Maruca vitrata). The trial was carried out at Kamboinsé in Central Burkina Faso. Seven cowpea varieties resistant to C. tomentosicollis were sprayed twice with neem seed extracts against thrips and pod borers, and compared to a productive and susceptible check variety sprayed with deltametrin and dimethoate. Results revealed that flower thrips and pod borer populations on the resistant varieties sprayed with neem seed extract were similar to the check variety sprayed with conventional insecticide. Most of the varieties resistant to C. tomentosicollis were less damaged than the susceptible variety sprayed with chemical insecticide. The grain yield of the variety KVx 908-1 (936 ± 541.65 kgha) was similar to the productive check variety sprayed with conventional insecticide. Results are discussed in the light of developing alternative strategies for the control of key cowpea insect pests.